THE EFFECTIVENESS AND FUTURE DIRECTIONS OF CPR SIMULATORS IN HEALTHCARE TRAINING - Parpibaeva D.A.; Ergashov N.Sh.; Salaeva M.S.; Salimova N.D.; Boltaboev X.Q.; Turbanova U.V. (Journals Park Publishing, 2023)
Non-alcoholic fatty liver disease (NAFLD) is a global health concern affecting up to 25% of the world's population. It is characterized by the accumulation of fat in the liver, which can lead to inflammation, fibrosis, and cirrhosis. The exact causes of NAFLD are not fully understood, but there is evidence to suggest that it is closely linked to obesity, insulin resistance, and metabolic syndrome. MicroRNAs (miRNAs) are small non-coding RNAs that play important roles in the regulation of gene expression. In recent years, there has been growing interest in the role of miRNAs, particularly miRNA-122, in the pathogenesis of NAFLD. NAFLD is a complex disease that can be divided into two subtypes: non-alcoholic fatty liver (NAFL) and non-alcoholic steatohepatitis (NASH). While NAFL is generally considered to be a benign condition, NASH can progress to advanced liver disease, including cirrhosis and hepatocellular carcinoma. MiRNA-122 is a liver-specific microRNA that plays an important role in the regulation of lipid metabolism and the development of nafld. Studies have shown that mirna-122 is downregulated in the livers of patients with nafld and animal models of the disease. This downregulation is thought to contribute to the development of NAFLD by altering lipid metabolism in the liver. MiRNA-122 regulates the expression of several genes involved in lipid metabolism, including fatty acid synthesis, β-oxidation, and cholesterol metabolism. In animal models of NAFLD, overexpression of miRNA-122 has been shown to reduce hepatic steatosis and inflammation, while inhibition of miRNA-122 exacerbates these features of the disease, suggesting that miRNA-122 plays a protective role in the development of NAFLD.